1995
DOI: 10.1055/s-2007-1013781
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Results with VDD Pacing in Patient with Atrioventricular Block

Abstract: In patients with intact sinus node function and atrioventricular block III(o) VDD pacing with a single pass lead may have advantages compared to conventional DDD systems. The purpose of this study was to evaluate the reliability of a new VDD pacemaker with regard to problems encountered with the implantation and the stability of the atrial sensing potential in the postoperative course. 24 patients (10 male, 14 female; age 61 +/- 17 years) underwent implantation of the Intermedics UNITY 292+07 VDD pacemaker. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Intermittent atrial undersensing is common in these pacemakers 11 . Previous studies have demonstrated a gradual decrease in the P wave amplitude during the follow‐up period 12−18 . Our study also demonstrated that in both pacing modes there were significant differences in atrial signal measurements in the period between implantation and the last visit ( P < 0.05).…”
Section: Discussionsupporting
confidence: 75%
“…Intermittent atrial undersensing is common in these pacemakers 11 . Previous studies have demonstrated a gradual decrease in the P wave amplitude during the follow‐up period 12−18 . Our study also demonstrated that in both pacing modes there were significant differences in atrial signal measurements in the period between implantation and the last visit ( P < 0.05).…”
Section: Discussionsupporting
confidence: 75%
“…Many studies showed stability of P wave amplitude in VDD systems in long‐term follow‐up 3,5‐7,9,14‐16 . However, P wave sensing failure can occur at times during the follow‐up in 5–13% of patients 5‐7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Single lead VDD pacing is a reliable method of physiological pacing and an established therapy in patients with atrioventricular (AV) block and normal sinus node function 1‐12 . According to current guidelines it is one of the recommend types of therapy 13 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations